Route of Vaccine Administration Influences the Impact of Fms-Like Tyrosine Kinase 3 Ligand (Flt3L) on Chlamydial-Specific Protective Immune Responses - Pais, Roshan; Omosun, Yusuf; Igietseme, Joseph U.; Fujihashi, Kohtaro; Eko, Francis O. (Frontiers in Immunology, 2019)
We tested the hypothesis that the impact of the Fms-like tyrosine kinase 3-ligand (Flt3L; FL) on recombinant Vibrio cholerae ghost (rVCG) vaccine-induced chlamydial immunity is influenced by route of vaccine delivery. Female C57BL/6J mice were immunized rectally (IR) or intramuscularly (IM) with rVCG co-expressing the Chlamydia trachomatis PmpD and PorB proteins (rVCG- PmpD/PorB) with and without FL or glycoprotein D of HSV-2 (rVCG-gD2) as antigen control. Vaccine evaluation was based on measurement of T cell proliferation, Th1/Th2 cytokine, and humoral responses at systemic and mucosal compartments, and protection against intravaginal challenge infection. Results revealed that high levels of CD4+ T cell-mediated and humoral immune responses, were elicited in mice as a function of both IR and IM immunization. Unexpectedly, co-administration of vaccine with FL enhanced specific Th1-type cytokine levels and T cell proliferative responses following IR but not IM immunization. While administration of vaccine with FL enhanced the specific mucosal and systemic IgA antibody responses following both immunization routes, IgG2c responses were not enhanced following IR delivery. The vaccine-induced immune effectors protected mice against live heterologous C. muridarum infection irrespective of route of vaccine administration, with the regimen incorporating FL having a protective advantage. Further evaluation showed that protection afforded by the FL adjuvanted vaccine was facilitated by CD4+ T cells, as indicated by reduction in the intensity and duration of genital chlamydial shedding by naïve mice following adoptive transfer of immune CD4+ T cells. Taken together, the results indicate that comparable protective immunity, which is enhanced by co-delivery with FL, is elicited in the female genital tract against Chlamydia infection after mucosal and systemic administration, highlighting the ability of FL to function as an effective immunostimulator at both mucosal and systemic sites. The differential modulation of humoral and cellular immune responses, and protective immunity afforded by the FL adjuvanted vaccine following IR administration indicates that the immunomodulatory impact of FL on chlamydial-specific immunity is influenced by the route of vaccine administration. Thus, targeting of VCG-based vaccines to antigen presenting cells by co-delivery with FL is a feasible immunization approach for inducing effective chlamydial immunity in the female genital tract.